The Use of Fishbone Diagram Technique to Improve Students’ Writing Ability - Usman Kasim; Nira Erdiana; Delfira Aulia (Proceedings of AICS - Social Sciences, 2021)
This is a library research which analyzes how the use of fishbone diagram technique can improve students’ writing ability and it focuses on Ishikawa’s theory with his 4 steps of fishbone diagram; preparation, drawing, identification, and produce. The data were collected using investigation technique of discourses from textbooks, articles, journals, papers and other relevant data sources. There are 6 sources in this study and those sources are: Ardianto (2019), Mahsunah and Durotun (2018), Al-Khataybeh (2018), Apriliya and Putri (2018), Razoqey and Yahya (2019), Safitri and Nanda (2016). Here, the researchers analyzed them by reading deeply to get understanding of the important data from all of the sources. The researchers also reviewed them to look for similarities or association between one source and another sources. After that, the researchers paraphrased and elaborated the statements to give valuable information. The findings from the selected data were explained and summarized by mentioning the name of the researcher, the methodology, the text types, learners background, areas, the procedure in teaching and learning process, and the results of the study. the result of the analysis from all the sources showed that the use of fishbone diagram technique could improve students’ writing ability based on four steps of this technique.Keywords: Fishbone diagram technique, writing, library research.